(untitled) (Materiali di Estetica. Terza serie, 2017)
The purpose of this note is to highlight the two fundamental aspects of the literary personality of Antonio Tabucchi. On the one hand, it appears conditioned by the aura of the great Portuguese poet Fernando Pessoa, to whom he has devoted a real intellectual passion. For the rest, he remains rooted in his Tuscan land of origin and the ethical-political education he has derived from.